2022
DOI: 10.3390/foods11070974
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of Ethanol Extract from Sanghuangporous vaninii in High-Fat/Sucrose Diet and Streptozotocin-Induced Diabetic Mice by Modulating Gut Microbiota

Abstract: Type 2 diabetes mellitus (T2DM) may lead to abnormally elevated blood glucose, lipid metabolism disorder, and low-grade inflammation. Besides, the development of T2DM is always accompanied by gut microbiota dysbiosis and metabolic dysfunction. In this study, the T2DM mice model was established by feeding a high-fat/sucrose diet combined with injecting a low dose of streptozotocin. Additionally, the effects of oral administration of ethanol extract from Sanghuangporous vaninii (SVE) on T2DM and its complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 85 publications
(89 reference statements)
0
22
0
Order By: Relevance
“…26 On the other hand, some recent studies showed that different extracts of “Sanghuang” could modulate intestinal microbiota imbalance to alleviate diabetes, including water extract (polysaccharide) of Phellinus linteus 26 and ethanol extract of Sanghuangporus vaninii . 27 Hence, this study established a T2DM mouse model to evaluate the effect of a mixture of different “Sanghuang” extracts on the biochemical indicators in T2DM mice, and the regulatory effect on the intestinal microbiota in T2DM mice was also analyzed through 16S rRNA sequencing. It also revealed the relationship between biochemical indicators and the intestinal microbiota, providing theoretical guidance for developing “Sanghuang” as a functional food to prevent T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…26 On the other hand, some recent studies showed that different extracts of “Sanghuang” could modulate intestinal microbiota imbalance to alleviate diabetes, including water extract (polysaccharide) of Phellinus linteus 26 and ethanol extract of Sanghuangporus vaninii . 27 Hence, this study established a T2DM mouse model to evaluate the effect of a mixture of different “Sanghuang” extracts on the biochemical indicators in T2DM mice, and the regulatory effect on the intestinal microbiota in T2DM mice was also analyzed through 16S rRNA sequencing. It also revealed the relationship between biochemical indicators and the intestinal microbiota, providing theoretical guidance for developing “Sanghuang” as a functional food to prevent T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intestinal microflora has received great attention, and its structure and stability are important for the maintenance of intestinal balance ( 40 ). Studies have shown that altering specific microorganisms in the intestine can affect the development of diabetes ( 41 , 42 ). In this study, 16S rRNA based sequencing analysis was conducted to investigate the effects of SVP on the structure of intestinal microflora.…”
Section: Resultsmentioning
confidence: 99%
“…As changes in food and nutritional status have a strong influence on body weight, this is one of the anthropometric measurements that is frequently used for assessing nutritional status [ 28 ]. Insulin deficiency in diabetics is known to disrupt protein and fat metabolism, resulting in weight loss ([ 59 ].…”
Section: Resultsmentioning
confidence: 99%